Beyond the assumptions: Religious schools and their influence on students' social and civic development. (March 2018) - Cross, Graeme; Campbell-Evans, Glenda; Gray, Jan
Are religious schools fit to prepare students with the social competencies required for life in a pluralistic society, or do they offer a sheltered school experience, which deprives them of adequate socialization opportunities? This question has emerged in public discourse in response to the growing presence of religious schools in many western democracies, including Australia, where their growth has been prolific in the past 30 years. In this article, the tensions around the place of religion within Australia's education system and the adequacy of religious schools to prepare students to contribute to the nation's social cohesion and pluralistic workplaces are investigated.